Anthropometric Indicators of Advanced Children with Natural and Artificial Nutrition - Usmonova Gulizora Bakhtiyorovna (Genius Journals, 2022)
The study of the growth, development and condition of the facial skeleton of a modern child can be a theoretical and methodological basis for the development and improvement of anthropometric methods of diagnosis and reconstruction in medicine, substantiation of new principles of prevention and treatment of vertebral anomalies and traumatological diseases. In the modern concept of orthopedic treatment, the main task is to achieve the desired results, taking into account individuality
Keywords: anthropometric indicators; children; artificial